The influence of diabetes on the quality of life and on the body image of elderly people who frequent nuclei of coexistence. - Batista, Raquel Fernandes; Nali, Luiz Henrique da Silva; Rosa, Eloi Francisco (Journal of Health Care, 2021)
Introduction: Diabetes is a prevalent disease in the Brazilian population and is a complicating factor in the quality of life of the elderly. In addition, obesity is one of the factors that predispose to diabetes and also is pointed out in the elderly body perception. Interestingly, the negative perception of the corporeal image can influence the development of obesity. Objectives: To identify the influence of diabetes on the quality of life and the perception of body image in the elderly. Methods: A cross-sectional research was carried out with a quantitative approach. Participants answered three questionnaires on the characterization of the sample profile to assess quality of life and body image perception. Diabetics answered a fourth questionnaire that assessed patients’ perspective on the impact of diabetes and treatment on their lives. Results: A total of 85 elderly people were included, 52 non-diabetic, 33 diabetic, 29 controlled with insulin. The results showed the quality of life between regular and good, considering the physical, psychological, social and environmental aspects. In the group of diabetics, satisfaction with the ability to work and performance in activities of daily living stood out. And for the perception of body image, the non-diabetic patient reported satisfaction with his own image, while diabetics presented a perceived and expected distance from body image. Conclusion: The disease may present a limiting influence on physical, emotional and social aspects, in addition to changing the perception of body image. However, elderly diabetics were more satisfied with performing basic daily activities.